Major spiders in vegetable ecosystem and their predatory potential - Manu P Mani (Department of Agricultural Entomology, College of Agriculture, 2005)
Spider faunistic survey conducted in okra, brinjal, cowpea, bittergourd and amaranthus fields in Kalliyoor panchayat of Thiruvananthapuram district during the summer of 2004, revealed the prevalence of high density and diversity of spiders in the vegetable ecosystem. Hunting spiders were dominant in all the vegetable plots. Thirty species of spiders distributed in nine families were recorded with the number of species in each vegetable field ranging from 10 to17. Among the thirty species, 16 species were commonly seen in the different vegetable fields while 14 species were seen exclusively associated with a particular vegetable. Araneidae with ten species was the most represented family in the vegetable fields followed by Oxyopidae and Salticidae. The other families observed were Miturgidae, Thomisidae, Tetragnathidae, Corinnidae, Lycosidae and Clubionidae. Most of the spiders appeared during the vegetative and flowering stages of the crop. Few spiders were recorded in the early stage of the crops. Four spiders viz., O. javanus, C. danieli, N. mukerjei and T. mandibulata were dominant in all the vegetable plots among which O. javanus and C. danieli predominated. Studies on the seasonal influence showed no significant difference in the abundance of the spiders during summer and rainy seasons. Rather, the growth stages of the crops significantly influenced the build up of the spider population with higher population being observed during the reproductive phase. In general, the spiders preferred soft bodied insects like the hemipterans, lepidopterans, dipterans and coleopterans (eggs and grubs) for predation. While the spiders did not show any significant preference for the different hemipteran prey in a mixed diet, significant difference was shown for the different lepidopteran pests. O. javanus had the maximum preference for the lepidopteran pests Chemical insecticides were more toxic to the spiders than botanicals when tested at their recommended doses. Among the chemical insecticides, dimethoate 0.05 per cent, carbaryl 0.2 per cent and malathion 0.1 per cent were highly toxic. Even at different doses the insecticides were toxic to the spiders. Quinalphos 0.05 per cent and imidacloprid were less toxic. Between the two methods of application, topical application of insecticides was more detrimental to the spiders than release on treated plants. Among the spiders, T. mandibulata was more susceptible to the insecticides followed by C. danieli. O. javanus and N. mukerjei were less sensitive.